Efforts To Prevent Criminal Acts Of Corruption By The Repbulic Of Indonesia Prosecutor Office Trough The Return Of State Financial Losess Reviewed From The Value Of Justice - Pratiwi, Rizky Ika; Pujiyono; Budi Ispriyarso (Universitas Negeri Semarang, 2025)
Corruption is a global challenge that crosses national borders and various sectors of development. This act of corruption is not only a threat to economic stability, but also becomes an obstacle in achieving sustainable development. The state has a responsibility to fulfill the rights to basic community needs in the context of public services. The Indonesian government, as mandated by the Constitution of the Republic of Indonesia regarding public services, has an obligation to build public trust in accordance with the demands and expectations of the community. This article discusses the problem of how the Prosecutor's Office attempts to recover state financial losses by perpetrators of criminal acts of corruption and the concept of recovering state financial losses based on the values ​​of welfare and justice. The method used in this writing is a normative research method. The results of this research are the efforts that can be taken by the Prosecutor's Office of the Republic of Indonesia to recover state financial losses caused by criminal acts of corruption, which can be started at the investigation stage. So that the implementation of a punishment based on the values ​​of welfare and justice will provide benefits to the state structure and improve the welfare of the Indonesian nation.